Pengaruh Kebijakan Dividen, Volume Perdagangan, Firm Size, Leverage, dan Earning Volatility terhadap Volatilitas Harga Saham pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2023–2025 - Karina Ratu Anisya; Chara Pratami Tidespania Tubarad (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The banking sector serves a pivotal function in propelling the IHSG on the Indonesia Stock Exchange (IDX), where its stock prices are influenced by various internal corporate factors. The 2023–2025 period was selected as the research context to depict post-pandemic equity market dynamics, regulatory shifts, and international geopolitical instability that triggered elevated stock price volatility. This study aims to evaluate the impact of dividend policy (dividend payout ratio and dividend yield), trading volume, firm size, leverage, and earning volatility on the stock price volatility of banking issuers listed on the Indonesia Stock Exchange during the 2023–2025 timeframe. A quantitative approach was applied utilizing secondary data from annual financial reports and stock prices. Through a purposive sampling technique, 18 companies were chosen, yielding of 54 observations. Data processing was conducted using panel data regression to evaluate the effect of independent variables on stock price volatility. The empirical findings reveal that the Dividend Payout Ratio (DPR) exerts an inverse impact on stock price volatility at a 5% significance level, whereas leverage and earnings volatility exert an inverse impact at a 10% significance level. Furthermore, Dividend Yield (DY) and trading volume demonstrate a direct and statistically meaningful effect on stock price volatility. In contrast, firm size displays no statistically meaningful effect. Concurrently, all independent variables statistically significantly affect stock price volatility. These empirical findings pinpoint the variables affecting stock price volatility along with their direction of impact, presenting vital considerations for management as well as investors in investment decision-making.